2012 IEEE International Conference on Development and Learning and Epigenetic Robotics (ICDL) 2012
DOI: 10.1109/devlrn.2012.6400583
|View full text |Cite
|
Sign up to set email alerts
|

Curiosity-driven phonetic learning

Abstract: Abstract-This article studies how developmental phonetic learning can be guided by pure curiosity-driven exploration, also called intrinsically motivated exploration. Phonetic learning refers here to learning how to control a vocal tract to reach acoustic goals. We compare three different exploration strategies for learning the auditory-motor inverse model: random motor exploration, random goal selection with reaching, and curiositydriven active goal selection with reaching. Using a realistic vocal tract model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…Such systems will naturally and spontaneously move from one stage of development to the next, from one level of complexity to another, as error reduction becomes less available (either all that's left is uninteresting noise or the complexity is yet too high to be managed given the skill level of the organism). A neat outcome of such systems is the self-organization of developmental and learning trajectories that naturally move agents from acquiring simple to more complex skills over time (Oudeyer and Kaplan 2006;Oudeyer et al 2007;Kaplan and Oudeyer 2011;Moulin-Frier and Oudeyer 2012).…”
Section: Novelty Seeking and Learning Progressmentioning
confidence: 99%
“…Such systems will naturally and spontaneously move from one stage of development to the next, from one level of complexity to another, as error reduction becomes less available (either all that's left is uninteresting noise or the complexity is yet too high to be managed given the skill level of the organism). A neat outcome of such systems is the self-organization of developmental and learning trajectories that naturally move agents from acquiring simple to more complex skills over time (Oudeyer and Kaplan 2006;Oudeyer et al 2007;Kaplan and Oudeyer 2011;Moulin-Frier and Oudeyer 2012).…”
Section: Novelty Seeking and Learning Progressmentioning
confidence: 99%
“…Instead of exploring in the space of motor parameters, babbling can also be organized in the space of outcomes [7], [8]. In [9] it was shown that such goal babbling can bootstrap vowel sounds quicker than motor babbling. Goal babbling has subsequently been successfully applied for learning F0 contours [10] or for modeling the emergence of speech-like sounds in general [11], [12].…”
Section: Introductionmentioning
confidence: 99%
“…Studies by Moulin-Frier et al [13], [14], [15], [16] have applied the idea of goal babbling to the speech domain. By using formant frequencies as goals, they could demonstrate the emergence of articulated speech sounds [16] and the bootstrapping of vowel sounds [13].…”
Section: Introductionmentioning
confidence: 99%
“…By using formant frequencies as goals, they could demonstrate the emergence of articulated speech sounds [16] and the bootstrapping of vowel sounds [13]. In a recent work [17], Liu and Xu used goal babbling to control F0 for Chinese language.…”
Section: Introductionmentioning
confidence: 99%